If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5x+14=x+13
We move all terms to the left:
-5x+14-(x+13)=0
We get rid of parentheses
-5x-x-13+14=0
We add all the numbers together, and all the variables
-6x+1=0
We move all terms containing x to the left, all other terms to the right
-6x=-1
x=-1/-6
x=1/6
| 2/5w=46/5 | | 5^x-1+5^x-2=-30 | | m+7(6m-4)=0 | | 4/7w=88/7 | | 5+6(2s+5)=0 | | 4x+14=-2x-22=12 | | 4/7w=124/7 | | d+7/12=11/12 | | 3(x+3)-11=0 | | z-7/20=9/20 | | 7k-7=0 | | 4(2x-6=56 | | 4(2x-6=-56 | | 3(2x-(+3x+1=x+1 | | 465,8a+3=321,7a-4 | | 5w+7=4-8w | | 3h²+47=0 | | (3x+-7)=-15x+35 | | |-3x+6=x–20–7x| | | -3x+6=x–20–7x | | 2m-(9m+6)=8 | | 47=-19+n | | 11x+15=-2x+2x | | 10m-7m+4)-5m=16 | | 10m(7m+4)-5m=16 | | 15-3.7m=12.85-2,5m | | (3x+2)/7=(4x-1)/5 | | 11x+15=-2x | | X^3-24x^2-64=0 | | -9y=4−10y | | 8x-9-(5x+30)=0 | | 6x²+7=17x |